Skladiščno-komisionirni sistemi - Lerher, Tone (University of Maribor Press, 2021)
Warehouses and Order-Picking Systems. The textbook deals with warehouses and order-picking systems in intralogistics with the basic warehouse functions. The most labour intensive and most challenged process in warehouses is order picking process, which is still mainly performed manually or is only partially automated. The order-picking process has received the most attention in literature and in practice, both from the standpoint of implementing effective order-picking methods and strategies and implementing automated and robotic technologies in the order-picking process for palletized goods, cartons, and individual items. The textbook specifically addresses automated storage and retrieval systems with analytical models for determining single- and dual-command cycle time and throughput performance of the warehouse.